Immunologic Studies on Pichinde Virus Infection in Cell Culture and in Syrian Hamsters - Buchmeier, Jospeh Michael (My University, 1976)
Infection by Pichinde virus, a member of the arenavirus group, was studied in vivo in Syrian hamsters, and in vitro in cell culture. Emphasis in the in vivo studies was placed on the mechanism of resistance to virus infection in adult hamsters. Two hamster strains were found to differ in their susceptibility to lethal Pichinde virus infection. LVG/Lak hamsters were found to be 100% susceptible to low doses of Pichinde virus during the first 6 days of life, but after 8 days of life, mortality was uncommon. Peak serum virus titers in animals infected at 3 days of life were 4 logs greater than in animals infected at 12 days. MHA/Lak hamsters, in contrast, were found to be susceptible to lethal virus infection both as newborns and as adults. Peak serum virus titers of greater than 10⁸ PFU/ml were observed 8 days after infection of adult MHA hamsters compared with less than 10³ PFU/ml in their LVG counterparts. Cultured primary kidney cells and peritoneal macrophages from either hamster strain supported Pichinde Virus replication equally well in vitro. Antibody levels measured by complement-fixation test were similar at 13, 21, and 30 days after infection. Cyclophosphamide immunosuppression, administered 3 days after infection, rendered adult LVG animals susceptible while slightly increasing the mortality among MHA hamsters. These findings suggest that immunologic factors maturing early in life in LVG hamsters and deficient in MHA hamsters limit Pichinde virus infection. The relationship of these observations with previously reported arenavirus diseases is discussed.
The antigenic structure of Pichinde virus was examined. Lysates of BHK₂₁ cells, infected with Pichinde virus and harvested 48-96 hours after infection contained virus-specific antigens detectable by complement-fixation (CF) test. Immunodiffusion analysis of the lysates demonstrated two antigens which differed in their properties of heat and proteolytic enzyme resistance. The antigen accounting for the major proportion of the CF antigen activity was a heat stable, pronase resistent protein of 20-30,000 molecular weight estimated by gel filtration. The minor antigen was heat labile and susceptible to proteolysis. Antiserum prepared against partially purified major antigen, yielded a band of identity when tested against antiserum prepared against virus "cores" obtained by NP-40 solubilization of purified Pichinde virus. Disruption of purified virus by treatment with 1% NP-40 and 50 ug/ml RNase liberated 2 soluble antigens which identified with those demonstrated in lysates of infected cells. The liberated antigenic activity was shown to contain 3 of the 4 polypeptides found in the virion. These findings suggested that the antigens detectable by CF and immunodiffusion were components of the virion core. Major antigen derived from infected cells was purified by rate-zonal sedimentation, isoelectric focusing and gel filtration. Two low molecular weight polypeptides were demonstrable in the purified antigen.
Since multiple segments of RNA exist in the Pichinde virion, it was of interest to determine, whether antigen synthesis and virus production could be dissociated in the infected cells. In Vero cells infected by Pichinde virus, antigen on the cell surface, and production of infectious virus shut down 48-96 hours after infection, whereas antigen detectable in the cytoplasm of infected cells appeared stable for over 5 days. In BHK₂₁ cells, actinomycin D (AD) at dosage levels of 1-4 ug/ml reduced virus yields by greater than 95% while reducing antigen detectable by CF by only 30%. The quantity of antigen produced was independent of AD dosage within the range tested. Both the major and the minor antigens were identified in lysates of AD treated cells. The observed decrease in infectious virus production could not be attributed to increased cell associated virus or to greater production of defective interferring particles. Surface antigen, demonstrable by immunofluorescence and by antibody binding assay was found to accumulate of infected cells incubated with AD. These findings suggest that Pichinde virus replication in AD treated BHK₂₁ cells is blocked at the level of virus maturation.
Keywords: Medical Sciences; Medical Sciences